Cyber stalking victimisation of women: Evaluating the effectiveness of current laws in India from restorative justice and therapeutic jurisprudential perspectives - Halder Debarati (Temida)
Victimisation of women through cyber stalking is one of the most serious crimes against women. Many countries including India have developed laws regulating cyber stalking. This article argues that since both, restorative justice (RJ) and therapeutic jurisprudence (TJ) are victim oriented, the issue of cyber stalking of women may be dealt with by RJ process and the laws in this regard must be analysed by the legal actors with a background in RJ and TJ philosophy. India had earlier taken up therapeutic punishment policy to enforce rights of the accused. But the modern principles of TJ have still not been considered in the RJ background in cyber stalking cases. This article therefore examines whether RJ and TJ principles can replace retributive principles for cyber stalking victimisation. It also examines the Indian cyber stalking law from RJ and TJ perspectives to assess its effectiveness for victims.